Action Research on Promoting Spatial Skills Development of Older Children in Block Play - FEIYAN, Li; HUI, Zhang; HONGMEI, Gou; GUIMEI, Jia (Journal of Research in Educational Sciences; Vol 14 No 16 (2023): JRES, Volume XIV, Issue 16, Winter 2023DO - 10.14505/jres.v14.16.01, 2023)
Spatial skills are an important part of human intelligence and have a profound impact on children's later learning and development of mathematics, and block play, as one of the most fundamental activities in kindergarten, has a positive effect on the development of children's spatial skills. In order to improve children's spatial skills through block play, this study used an action research paradigm to intervene with 30 children in the experimental and control classes over a period of three months. In quantitative terms, the spatial skills of the children in the experimental class showed significant improvements in comparison with those in the control class. In terms of quality, the children in the experimental class used significantly more spatial language in their block play and their level of construction improved significantly. Problem solving skills were developed and interest in constructing was increased during collaborative construction. Teachers who participated in the action research were less 'resistant' to the role of the teacher in block play, and their ability to use block play as a guide for children's spatial skills development was improved. The collaboration of the research team members was a key factor in the success of the action research. Teachers should use different types of block play to improve children's construction skills. Promote peer block building to bring out the unique value of peer construction. Focus on the role of spatial language and encourage children to use it to communicate.